PENGETAHUAN IBU TENTANG KEPUTIHAN DI KOTA MANADO - Fadilla, Emi; Mewengkang, Maya; Wantania, John (e-CliniC, 2014)
Abstract: Reproductive organs is one of the organs that are sensitive and require special care.Vaginal discharge is the health common problems of women genital area. The purpose of this research is to determine the knowledge of vaginal discharge  and the relationship between the factors that affect the mother's knowledge about vaginal discharge .This research used observational analytic method with a cross sectional study trough primary data based on questionnaires. From 200 respondents,  there were 7 respondents with a poor knowledge , 39 respondents with a moderete knowledge, and 154 respondents with a good knowledge. There is no significant relationship between mother's level of knowledge about vaginal discharge and age (p-value = 0.171), education (p-value = 0.090) ,  resources (p value = 0.174) and experience (p value = 0.052). There is a significant relationship between the level of knowledge about vaginal discharge and occupation (p value = 0.000). Mother’s knowledge of vaginal discharge in manado city is good. In this research only occupation has a significant relationship with the level of knowledge about vaginal discharge. Key words: vaginal discharge,knowledge   Abstrak: Organ reproduksi merupakan salah satu organ tubuh yang sensitif dan memerlukan perawatan khusus. Masalah kesehatan area genital yang umum terjadi pada wanita adalah keputihan. Tujuan penelitian ini mengetahui pengetahuan ibu tentang keputihan dan hubungan antara faktor-faktor yang mempengaruhi tingkat pengetahuan ibu tentang keputihan.Penelitian ini menggunakan metode observasional analitik dengan studi cross sectional menggunakan data primer berdasarkan kuesioner.Dari 200 responden penelitian didapatkan 7 responden dengan pengetahuan kurang, 39 responden dengan pengetahuan cukup (sedang), dan 154 responden dengan pengetahuan baik. Tidak ada hubungan bermakna antara tingkat pengetahuan dengan umur (nilai p = 0,171), pendidikan (nilai p = 0,090), sumber informasi (nilai p = 0,174) dan pengalaman ( nilai p = 0,052). Ada hubungan yang bermakna antara faktor pekerjaan (dengan nilai p = 0,000)  dengan tingkat pengetahuan ibu tentang keputihan.Pengetahuan ibu tentang keputihan di kota Manado adalah baik.  Pada penelitian ini hanya pekerjaan yang memiliki hubungan bermakna dengan tingkat pengetahuan ibu tentang keputihan. Kata kunci: keputihan, pengetahuan.